2002
DOI: 10.1002/1521-3994(200208)323:3/4<357::aid-asna357>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

A new look at dynamo cycle amplitudes

Abstract: We explore the dependence of the amplitude of stellar dynamo cycle variability (as seen in the Mount Wilson Ca II HK timeseries data) on other stellar parameters. We find that the fractional cycle amplitude Acyc (i.e. the ratio of the peakto-peak variation to the average) decreases somewhat with mean activity, increases with decreasing effective temperature, but is not correlated with inverse Rossby number Ro −1 . We find that Acyc increases with the ratio of cycle and rotational frequencies ωcyc/Ω along two, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
58
5

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(68 citation statements)
references
References 9 publications
(16 reference statements)
5
58
5
Order By: Relevance
“…However, we found a small anti-correlation between the contrast C and the Rossby number (see Fig. 9); this result does not agree with the results of Saar & Brandenburg (2002) who did not find any clear correlation between the cycle amplitude and Ro.…”
Section: Rossby Numbercontrasting
confidence: 99%
See 3 more Smart Citations
“…However, we found a small anti-correlation between the contrast C and the Rossby number (see Fig. 9); this result does not agree with the results of Saar & Brandenburg (2002) who did not find any clear correlation between the cycle amplitude and Ro.…”
Section: Rossby Numbercontrasting
confidence: 99%
“…At first sight no clear correlation appears, but if we look at the stars that show evidence of long-lived features (red triangles), a slight correlation seems to be present. Saar & Brandenburg (2002) observed the opposite, that there was an anti-correlation, but we note that their result concerns stars where they observed magnetic cycles while our subsample only shows long-lived features.…”
Section: Magnetic Index and Other Parameterscontrasting
confidence: 61%
See 2 more Smart Citations
“…This illustrates that the use of fractional amplitudes obscures the fact that the more active, faster rotators in general have a much larger variability than the Sun, which indicates a much more efficient dynamo. Indeed, Saar & Brandenburg (2002) studied cycle amplitudes for a stellar ensemble and found that ∆R HK / R HK ∝ R HK −0.23 , fractional amplitude decreases with increased activity. In an upcoming work we will use the longer timeseries available today to reexamine cycle properties such as amplitude and period for an ensemble of solar analogs.…”
Section: Linearity Of S With Kmentioning
confidence: 99%